Strategi Peningkatan Pelayanan Kesehatan Melalui Standarisasi Kamar Rawat Inap di RSUD Dolopo Kabupaten Madiun Berdasarkan Pp No. 47 Tahun 2021 Tentang Penyelenggaraan Bidang Perumahsakitan - Hadi, Purnomo; Rokhim, Abdul; Muhibbin, Muhammad (Jurnal Locus Penelitian dan Pengabdian, 2025)
In January 2014, BPJS Kesehatan launched the National Health Insurance (JKN) program, which brings together several previously fragmented health insurance programs, including Askes (covering public formal sector employees), Jamsostek (private formal sector workers), and Jamkesmas. In the JKN roadmap, Universal Health Coverage (UHC) was expected to be achieved by 2019, but UHC was not achieved until 2024. One of the targets is the same package of medical and non-medical benefits (class of care). This is also stated in Article 23 Paragraph 4 of UU No.40 of 2004 concerning the National Social Security System (SJSN) which mandates standard class treatment for JKN-KIS participants who require hospitalization in the hospital. In July 2023 Madiun Regency will have Universal Health Coverage (UHC) reaching 95.81%. The issuance of PP No. 47 of 2021 concerning Hospital as an implementation of Law No. 11 of 2020 concerning job creation, has an impact on bed rules in hospital inpatient services for JKN participant patients. The abolition of the class-based inpatient concept was replaced by the Standard Inpatient Class (KRIS) service with 12 indicators that must be met according to the Decree of the Director General of Health Services No. HK/02.02/I/1811/2022, where hospitals owned by the central and regional governments must provide at least 60% of all beds as standard inpatient rooms (KRIS). RSUD Dolopo has a capacity of 195 beds, with KRIS hospitalization of 86 TT or only 44% availability. The 44% still does not fulfill 100% of the 12 KRIS criteria. This means that Dolopo Hospital must provide at least an additional 31 TTs. If calculated according to the KRIS standard of 1 room with 4 TT, it means that RSUD Dolopo needs to provide at least 8 inpatient treatment rooms to fulfill the requirement. Based on this research, these obstacles cannot be resolved in a short time. Limitations in budget preparation and in the implementation of development must go through government procurement are obstacles for government hospitals to complete in a short time. In addition, budget availability is often a dilemma for hospitals in prioritizing budget use. In addition to the above, limited human resources in inpatient services are also often a major obstacle. The procurement of employees in government agencies must follow the rules and the number is very limited. In addition, the availability of budget in meeting the qualifications of Human Resources for training is more or less an obstacle. Another obstacle faced by Dolopo Hospital and hospitals in general is inconsistent regulations. There have been three changes in the implementation of the Standard Inpatient Room regulation. Starting in December 2020, it was postponed again on January 1, 2023 and finally on June 30, 2025.